STUDY OF SUITABILITY AND ENVIRONMENTAL CARRYING CAPACITY FOR BARRAMUNDI (Lates calcarifer. Bloch) CULTURE IN WATERS OF LEMUKUTAN ISLAND AND PENATA BESAR ISLAND, BENGKAYANG REGION, WEST KALIMANTAN - Shubhi, Muhammad Zamhar Auli; Kusumadewi, Yohana S; Suswati, Denah (Jurusan Perikanan dan Kelautan, 2017)
The aim of this research are to study location suitability for developing Asian Seabass culture with floating cage culture system based on carrying capacity at Lemukutan Island and Penata Besar Island. The methods of this research include : field survey for assessing the biophysics characteristic of Lemukutan and Penata Besar Island, Geographycal Information System for suitability analyze and carrying capacity analyze which compare to Kepmen LH No. 51 Years 2004.Â The results indicated that all the water quality parameters mostly good and suitable to support Asian Seabass culture. GIS results indicated that 1.564 Ha can be developed for Asian Seabass culture on the floating net cage, or arround 14,44% from the total 10.830,7 Ha with depth about more than 6 metres and less than 25 metres. Limited factor are sheltered area from the wave, wind and storm, current rate are generally more than 0,6 m/s and depth water some less than 6 m and more than 25 m.Â